Diseases impact the performance of maize hybrids in southern Minas Gerais - Guilherme Vieira Pimentel; Luiz Daniel Rodrigues da Silva; Natalia Costa; Amanda Santana; Elisabete da Cruz Silva Watanabe; Silvino Guimarães Moreira (Revista Agrogeoambiental)
Maize (Zea mays L.) generates profitability for rural producers, but grain productivity is still limited due to factors such as choosing a hybrid resistant to the main diseases that cause foliar and pre-harvest damage. Thus, the objective was to evaluate the agronomic performance and the reaction to the attack of brown eye spot, white spot, ear rot complex and the health of grains of maize hybrids. The experimental design was randomized blocks (DBC), with treatments consisting of eight maize hybrids (DKB 390, DKB 230, DKB 177, 30F53, KWS 9110, KWS 9006, KWS 9004 and Supremo), in five replications. The evaluated traits were: severity (%) of foliar and ear diseases, incidence (%) of pathogens in grains, plant and ear height, yield, weight of 100 grains and final stand. There were significant differences among the hybrids for plant height (PH), yield (Y), and 100-grain weight (GW). The most severe foliar damages were caused by Cercospora zeae-maydis and Pantoea ananatis. Fusarium graminearum showed an incidence of over 80% in grains, except for DKB 390 and KWS 9110. Hybrids DKB 177 and KWS 9006 showed high grain productivity and satisfactory levels of disease resistance.